Rasa Sebagai Prinsip Pertama Ontologi Harmoni dalam Pathet Pergelaran Wayang - Reno Wikandaru; L. Lasiyo; Suminto A. Sayuti (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2018)
This study aims to find and critically analyze the first principle of harmony in the wayang performance’s concept of pathet. The wayang performance’s concept of pathet as a material object which is analyzed from the perspective of the ontology as a formal object. The methodical elements of the study used include interpretation, induction, and deduction, internal coherence, holistic, historical continuity, idealization, comparison, heuristics, inclusive or analogous language, and description. The results of the study indicate that pathet is a concept that has an important position in the performance of wayang. Philosophically, pathet has many function and meaning. First, pathet is a representation of the structure of wayang performances. Second, pathet is the reference to the sound space in musical instruments. Third, pathet is the atmosphere builder or atmosphere of wayang performances. Fourth, pathet is a guide to the mastermind in building the aesthetic of wayang performance. Pathet, in addition, to have a function also consist of philosophical meaning. First, pathet as an aesthetic manifestation in puppet shows. Second, pathet is a symbol of the stages in human life. Third, pathet as a representation of the cosmic cycle. The investigation of pathet from the perspective of ontology yields the following conclusions. First, the concept of pathet is a representation of the concept of harmony in wayang performance. “Rasa” is the first principle of harmony in the wayang performance’s concept of pathet. This “rasa” has a spiritual dimension so that the ontology of harmony, in this case, is spiritualism. The dynamics of harmony moves with the law of “empan papan”, towards the ultimate goal of reality, namely the perfection of life. Ontology of harmony in the pathet of wayang performances shows monistic-spiritualistic thinking.